Measles outbreak after 12 years without endemic transmission, Portugal, February to May 2017 - George, Francisco (2018)
We report a measles outbreak in two Portuguese health regions (Algarve and Lisbon and the Tagus Valley) since February 2017, and which by 31 May resulted in 28 confirmed cases, of which 16 were unvaccinated. Thirteen cases were healthcare workers. One unvaccinated teenager died. Genotype B3 was identified in 14 cases from both regions. This outbreak occurs after 12 years without endemic measles transmission, and in a context of high measles vaccination coverage and immunity.